Helping Children Hear: Teachers’ Experiences of Using Soundfield Amplification Systems - Pauline Dickinson; Lanuola Asiasiga (New Zealand Journal of Teachers' Work)
The purpose of the evaluation was to assess the quality and success of the implementation of Soundfield Amplification Systems (SAS) in primary schools in Hawke’s Bay, where audiometry failure rates at school entry are generally higher than overall national rates and are particularly high for Māori and Pacific children who are at greater risk for otitis media. Process evaluation findings indicated the project was evidence-based and well-implemented. Early successes were: increase in ability of teachers to get and maintain students’ attention; decrease in teacher vocal fatigue; increase in student ability to follow oral instructions; and, decrease in teacher repetition of instructions.